2009
DOI: 10.4161/cc.8.15.9082
|View full text |Cite
|
Sign up to set email alerts
|

The active form of the metabolic sensor AMP-activated protein kinase α (AMPKα) directly binds the mitotic apparatus and travels from centrosomes to the spindle midzone during mitosis and cytokinesis

Abstract: (2009) The active form of the metabolic sensor AMP-activated protein kinase α (AMPKα) directly binds the mitotic apparatus and travels from centrosomes to the spindle midzone during mitosis and cytokinesis, Cell Cycle, 8:15, 2385Cycle, 8:15, -2398 The metabolic rheostat AMP-activated protein kinase (AMPK) is unexpectedly required for proper cell division and faithful chromosomal segregation during mitosis. Although it is conceptually attractive to assume that AMPK-interpreted microenvironmental bioenergetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
70
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 52 publications
17
70
0
Order By: Relevance
“…18 This finding not only reveals that a non-metabolic function of AMPKα at centrosomes may be to sense and respond to structural or functional inactivation of the mitotic spindle but further supports the idea that both the cycling activation of AMPK at each mitotic onset and the pre-activated state of AMPKα during all the phases of a perturbed mitosis allows a mechanism readyto-act in response to bioenergetic stress and/or mitotic spindle impairment in the next G 1 phase of the cell cycle. such as the centrosomal Aurora A kinase and the chromosomal passenger proteins (CPPs) Aurora B and INCENP: 15,16 -Loss or depletion of these mitotic kinases produces phenocopies of the mitotic defects observed in cells lacking AMPK, including defects in chromosome segregation and failures in cytokinesis.…”
Section: Ampkmentioning
confidence: 99%
See 1 more Smart Citation
“…18 This finding not only reveals that a non-metabolic function of AMPKα at centrosomes may be to sense and respond to structural or functional inactivation of the mitotic spindle but further supports the idea that both the cycling activation of AMPK at each mitotic onset and the pre-activated state of AMPKα during all the phases of a perturbed mitosis allows a mechanism readyto-act in response to bioenergetic stress and/or mitotic spindle impairment in the next G 1 phase of the cell cycle. such as the centrosomal Aurora A kinase and the chromosomal passenger proteins (CPPs) Aurora B and INCENP: 15,16 -Loss or depletion of these mitotic kinases produces phenocopies of the mitotic defects observed in cells lacking AMPK, including defects in chromosome segregation and failures in cytokinesis.…”
Section: Ampkmentioning
confidence: 99%
“…15,16 PP-AMPKα Thr172 , in an autonomous manner from AMPK regulatory subunits β and γ, physically associates with the mitotic apparatus to exhibit both centrosomal (i.e., Aurora A-like) and spindle midzone (i.e., CPP-like) localizations during mitosis and cytokinesis. 18 PP-AMPKα Thr172 localises at the poles of the mitotic spindle, adjacent to centrosomal Aurora A kinase in early mitosis, where it persists until late anaphase/telophase. In late mitosis, P-AMPKα Thr172 localises adjacent to the chromosomal passenger proteins Aurora B and INCENP at the central spindle midzone, and remains associated with the midbody in cytokinesis.…”
Section: Ampkmentioning
confidence: 99%
“…13 In this regard, we have previously reported that the active form of AMPK directly binds the mitotic apparatus and travels from centrosomes to the spindle midzone during mitosis. [32][33][34] Recently, we have established that polo-like kinase 1 (PLK1) is a novel regulator of AMPK activation at the mitotic apparatus. 35 These findings, altogether, may suggest the existence of a functional link connecting PLK1, AMPK and P-Raptor Ser722 during mitosis.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…However, in the absence of sustained energy supply, the gradually declining energy reserves will eventually arrest the cell cycle at the G2/M checkpoint; recent studies have shown that the mitotic machinery involves a metabolic sensor, the AMP-activated protein kinase, 20 which binds to various structures of the mitotic apparatus, including centrosomes, spindle poles and the spindle midzone. 21 This mechanism is understood as an energy gauge that assures that the cell disposes of sufficient energy to complete faithful chromosome separation and thus exerts an important cytokinetic suppressor function. 22 It is hence conceivable that mitotic activity continues in resection specimen up to the G2/M checkpoint, and that in the absence of sufficient energy reserves, tumor cells arrest in metaphase, where they are easily identified and counted by the diagnosing pathologist.…”
Section: Discussionmentioning
confidence: 99%